PRODUCTION OF BIOGAS FROM CO-DIGESTION OF COW DUNG, CHICKEN DROPPING AND COW RUMEN WASTES (FUDMA JOURNAL OF SCIENCES, 2022)
The increased use of fossil fuels for energy consumption has caused environmental problems both locally and globally. This study investigates the anaerobic digestion in the production of biogas, a renewable energy from the digestion and co-digestion of three different types of biodegradable wastes available in Katsina (cow dung, chicken droppings and cow rumen waste) as an alternative for fossil fuels for energy consumption. This was carried out using a 25 Litres capacity plastic keg, constructed to investigate the anaerobic digestion in generating biogas. The experiment was batch operated and the digester was charged with 10 kg of each waste was mixed with 10 kg (10L) of water and loaded into six different batch type biogas plants. Biogas production was measured for a period of 15 days and at an average temperature of 370C. The average biogas production from poultry droppings, cow dung, cow rumen wastes, mixture of cow dung/cow rumen wastes, cow dung/chicken droppings and cow rumen wastes/chicken droppings was found to be 210 cm3/kg, 160 cm3/kg, and 520 cm3/kg, 375cm3/kg, 470 cm3/kg, 390cm3/kg, respectively. During the digestion period, the volume of biogas production and the changes in pH indicate that the pH decreases as the retention period increases. The study recommends that biogas is not just a renewable energy source but also an appropriate way of managing waste, having potential to replace fossil fuel.
Keywords: biodegradable wastes, cow dung, cow rumen wastes, retention period